Untying the Relocation Knot: Recent Developments and a Model for Change - Ford, Chris (Columbia Journal of Gender and Law, 1997)
Relocation jurisprudence is a critical women’s law issue. Women are awarded primary custody of their children in the vast majority of divorce cases. The post-divorce family unit, comprised of the custodial parent and children, typically faces decisions about whether to relocate. Most of these relocation decisions stem from economic necessity or a custodial parent’s remarriage. A state that makes relocation difficult forces the custodial parent to make the unenviable choice of either pursuing a new opportunity in a different location, which may result in a loss of custody, or foregoing the opportunity and staying in the same locality in order to maintain custody. States that make relocation easier, on the other hand, have come to respect the custodial parent’s decision to move and have recognized the importance of maintaining the stable custodial relationship that has developed subsequent to the initial custody determination. How a state responds to relocation through its legal apparatus thus implicates the financial and emotional well-being of the post-divorce family.